1991
DOI: 10.1126/science.252.5009.1179
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X Genotype Characterized by an Unstable Region of DNA

Abstract: DNA sequences have been located at the fragile X site by in situ hybridization and by the mapping of breakpoints in two somatic cell hybrids that were constructed to break at the fragile site. These hybrids were found to have breakpoints in a common 5-kilobase Eco RI restriction fragment. When this fragment was used as a probe on the chromosomal DNA of normal and fragile X genotype individuals, alterations in the mobility of the sequences detected by the probe were found only in fragile X genotype DNA. These s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
372
1
17

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 725 publications
(402 citation statements)
references
References 4 publications
12
372
1
17
Order By: Relevance
“…FX311 was a fragile X-negative male, and showed normal size of the restriction fragment. These results were consistent with the ones reported by other groups (Verkerk et al, 1991 ;Yu et al, 1991 ;Kremer et aL, 1991), and any size variations in the restriction fragments were not observed among normal DNA samples in our assay conditions.…”
Section: Southern Blot Analysissupporting
confidence: 94%
See 1 more Smart Citation
“…FX311 was a fragile X-negative male, and showed normal size of the restriction fragment. These results were consistent with the ones reported by other groups (Verkerk et al, 1991 ;Yu et al, 1991 ;Kremer et aL, 1991), and any size variations in the restriction fragments were not observed among normal DNA samples in our assay conditions.…”
Section: Southern Blot Analysissupporting
confidence: 94%
“…The somatic variations observed in the affected patients might be the consequence of unequal sister chromatid exchange after DNA replication of the mutated X chromosome. In addition we observed in our preliminary experiments on fragile X families that the size of PstI-fragments were increased when the mutant chromosomes were transmitted by females, but not were increased when transmitted by males as previously reported by Yu et aL (1991).…”
Section: Southern Blot Analysissupporting
confidence: 85%
“…Fragile X syndrome has been found to be caused by expansion of a CGG trinucleotide repeat in the 5'-UTR Oberle et al, 1991;Yu et al, 1991;Verkerk et al, 1991), while expansion of a CTG trinucleotide repeat in the T-UTR has been identified in myotonic dystrophy (Mahadevan et al, 1992;Fu et al, 1992;Brook et al, 1992). Expansion of an intronic GAA trinucleotide repeat has recently been identified in Friedreich's ataxia (Campuzano et al, 1996).…”
Section: Four Classes Of Triplet Repeat Diseases Classified Based On mentioning
confidence: 99%
“…Fragile X syndrome is an X-linked recessive disease and the leading cause for mental retardation in male Oberle et al, 1991;Yu et al, 1991;Verkerk et al, 1991). Friedreich's ataxia is an autosomal recessive neurodegenerative disorder characterized by ata• decreased or absent tendon reflexes and impairment of deep sensation (Campuzano et al, 1996).…”
Section: Four Classes Of Triplet Repeat Diseases Classified Based On mentioning
confidence: 99%
See 1 more Smart Citation